Cure study of epoxy resin reinforced with multiwalled carbon nanotubes by Raman and luminescence spectroscopy. Issue 1 (27th April 2012) - Cividanes, L. S.; Brunelli, D. D.; Antunes, E. F.; Corat, E. J.; Sakane, K. K.; Thim, G. P.
Abstract Carbon nanotubes (CNTs) were annealed at high temperature under vacuum, followed by a chemical treatment using acids and ethylenediamine. The presence of acid and amine chemical groups on CNT surface was confirmed by infrared spectra. The amount of iron remaining in the CNTs after the treatments was evaluated by thermogravimetry and by energy dispersion spectroscopy. The crystalline property of CNTs was evaluated by Raman spectroscopy, showing that the acid treatment performed after the thermal treatment did not damage the nanotubes walls. Micrographs showed that the most dispersed CNTs were obtained after the amine functionalization step. The curing process of the neat resin and composites was studied by Raman and Luminescence spectroscopies and both techniques showed similar results. The presence of CNTs, functionalized or not, increased the cure degree of the epoxy resin when the same cure time was used in the comparison. Nanocomposites synthesized with annealed CNT and acid‐treated CNT had cure rates considerably higher at the beginning of the reaction. The difference in the cure rate was explained by means of the sample's homogeneity and the presence of chemical groups. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012